Distribution pattern of tree species from tropical to temperate regions in Makawanpur district, central Nepal - Bhattarai, S.; Bhatta, B.; Tamang, R. (Banko Janakari, 2018)
Tree species are the dominant component of forest ecosystems which influence most structural and functional attributes of these ecosystems. This study aims to document distribution pattern of forest types and their composition from tropical region at Hetauda (550 m asl) to temperate region above Simbhangyang (2500 m asl) of Makawanpur district, central Nepal. The carbon stock in the living biomass of tree species was estimated using an allometric equation while the biodiversity index was calculated using Shannon-Wiener Biodiversity index. A total of 62 species of trees belonging to 51 genera was recorded. Shorea forest was dominant in lower elevation while Quercus forest, Alnus-Rhododendron, Quercus-Lyonia and Quercus-Symplocos forests at higher elevation. Similarly, Castanopsis tribuloides has the widest distribution range (570 m to 2240 m asl) followed by Shorea robusta, Lagerstroemia parviflora, Trichilia connaroides, Syzigium jambos, Castanopsis indica, Schima wallichii etc. The highest number of tree species was recorded at 550 m elevation. Estimated carbon stocks were ranged from 0.85 — 53.37 t/ha with the mean value 24.98 t/ha. The values of Shannon-Wiener Biodiversity index ranged from 1.23— 2.78. There was positive relationship between carbon stock and biodiversity index (R2 = 0.40, p = 0.03). People have been practicing community forest management to support sustainability of harvesting in the study area. Banko Janakari A Journal of Forestry Information for Nepal Vol. 28, No. 1, 2018, page: 20-25